Clinical and Pathological Features of Solid Pseudopapillary Neoplasms of the Pancreas: A Nationwide Multicenter Study in Japan. Issue 8 (September 2018) - Hanada, Keiji; Kurihara, Keisuke; Itoi, Takao; Katanuma, Akio; Sasaki, Tamito; Hara, Kazuo; Nakamura, Masafumi; Kimura, Wataru; Suzuki, Yutaka; Sugiyama, Masanori; Ohike, Nobuyuki; Fukushima, Noriyoshi; et al.
Abstract : Objective: The aim of this study was to evaluate the clinicopathological features of solid pseudopapillary neoplasms (SPNs). Methods: In this retrospective study, 288 SPNs were analyzed. Results: Overall, 214 patients (74%) were female. Distant metastases occurred in 4 patients, and splenic vein tumor thrombus occurred in 1 patient. Although imaging findings showed large (>2.0 cm) SPNs with clear, regular border, and heterogeneous internal structure, small SPNs appeared as almost entirely solid. Surgical resection was performed in 278 cases. The 5-year survival rate was 98.8%. Six patients had tumor recurrence after the initial resection. The detection rate in typical pathological findings was low for small SPNs. Tumor extension to the pancreatic parenchyma was detected in greater than 70% of the cases. Tumor invasion to adjacent organs was detected in 13 cases. One was given a diagnosis of apparent high-grade malignant transformation. Conclusions: The proportion of male cases was higher than that in previous studies, and there were statistically significant differences in the onset age and tumor diameter between male and female patients. Therefore, women seemed to have an early occurrence of SPNs, suggesting a difference in the developmental stage between men and women. Images and pathological findings of SPNs varied according to tumor size. Our findings indicated that SPN patients have excellent survival after margin-negative surgical resection. Abstract : Supplemental digital content is available in the text.